Awareness and Practice of Deep Margin Elevation among Dental Practitioners in India: A Cross-Sectional Survey - Mythri Padaru; Preethesh Shetty; Namith Rai; Raksha Bhat (Pesquisa Brasileira em Odontopediatria e Clínica Integrada)
Objective: To evaluate knowledge, attitude and practice of deep margin elevation (DME) amongst dental practitioners in India, thereby increasing awareness. Material and Methods: A cross-sectional study was carried out among academicians, private practitioners, and post-graduate students, comprising 266 participants. Twenty-three close-ended web-based questionnaires were circulated through Google Forms. Data was analyzed using the Chi-square test, and descriptive analysis was performed using the Statistical Package for the Social Sciences software. Results: Although most respondents were aware of DME, only 27.4% claimed to have used this approach in daily practice. 60.4% reasoned out that DME was a technique-sensitive procedure. However, 50% of participants prefer to use DME as a substitute for surgical crown lengthening. There was a significant association between awareness regarding the term DME, knowledge of the procedure, and the study participants' cadre (p=0.024 and p=0.214, respectively). Conclusion: Knowledge, attitude, and practice of DME among dental practitioners in India are adequate. However, few dentists use this method to treat extensive subgingival decay in clinical practice. This can be attributed to the lack of literature on the subject and the perceived difficulties of the procedure. There is a need for more clinical research to understand the long-term prognosis of teeth restored using this technique and to encourage its usage in practice.